1998
DOI: 10.1007/s12130-998-1016-7
|View full text |Cite
|
Sign up to set email alerts
|

A model for the study of research and education in a transdisciplinary context

Abstract: In an evaluation project at the Goteborg University, we have looked at the relationship between individual and collective production of knowledge within the Health sciences in order to facilitate a common ground for a Academy of Health Sciences. We found obstacles for developing an environment which could stimulate multilateral co-operation and creativity. Some of these obstacles have their root in the different cultural backgrounds indicated in the analysis and makes it difficult to find common aims and strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Medical faculties, in contrast to the more behavioural approach at departments of nursing, have traditionally based their education on biological research, thus representing different paradigms in health care and resulting in different values among professionals [26,27]. Thus, there are differences in professional education and social influences within each profession.…”
Section: Discussionmentioning
confidence: 99%
“…Medical faculties, in contrast to the more behavioural approach at departments of nursing, have traditionally based their education on biological research, thus representing different paradigms in health care and resulting in different values among professionals [26,27]. Thus, there are differences in professional education and social influences within each profession.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of GIS knowledge is related to problems and perspectives of other sectors and disciplines, data management and data use. The difficulty for different disciplines to understand each other, and the negative consequences related to practical and scientific development, is not a new discussion (Hultberg et al, 1998). Concerning data management, Yeh (2005) concluded that the main constraints for the use of GIS in urban planning are not technical, but linked to the availability of data, staffing and need for reorganisation.…”
Section: Lack Of Knowledgementioning
confidence: 99%